Relationship between Dietary Fat Intake, Its Major Food Sources and Assisted Reproduction Parameters - A Kazemi; F Ramezanzadeh; MH Nasr-Esfahani (JRI, 2014)
Background: High dietary fat consumption may alter oocyte development and embryonic development. This prospective study was conducted to determine the relation between dietary fat consumption level, its food sources and the assisted reproduction parameters. Methods: A prospective study was conducted on 240 infertile women. In assisted reproduction treatment cycle, fat consumption and major food sources over the previous three months were identified. The number of retrieved oocytes, metaphase ΙΙ stage oocytes numbers, fertilization rate, embryo quality and clinical pregnancy rate were also determined. The data were analyzed using multiple regression, binary logistic regression, chi-square and t-test. The p-value of less than 0.05 was considered significant. Results: Total fat intake adjusted for age, body mass index, physical activity and etiology of infertility was positively associated with the number of retrieved oocytes and inversely associated with the high embryo quality rate. An inverse association was observed between sausage and turkey ham intake and the number of retrieved oocytes. Also, oil intake level had an inverse association with good cleavage rate. Conclusion: The results revealed that higher levels of fat consumption tend to increase the number of retrieved oocytes and were adversely related to embryonic development. Among food sources of fat, vegetable oil, sausage and turkey ham intake may adversely affect assisted reproduction parameters.